Effectiveness of TikTok-Based Health Education in Improving Pregnant Women's Knowledge of Abortion Prevention: A Quasi-Experimental Study - Ruwayda Ruwayda; Isnawati Isnawati; Yuli Suryanti (Journal of Community Health Provision, 2026)
Pregnant women's knowledge regarding abortion prevention remains an important determinant in reducing the risk of maternal morbidity associated with abortion. The rapid growth of social media has created new opportunities to deliver health education through engaging and accessible platforms such as TikTok. This study aimed to analyze the effect of TikTok-based health education on pregnant women's knowledge regarding abortion prevention at Sultan Thaha Saifuddin Regional General Hospital, Tebo Regency. A quasi-experimental one-group pretest-posttest study was conducted at the hospital's Obstetric Clinic in February 2026. Thirty-five pregnant women were recruited using accidental sampling. Participants received standardized educational videos on abortion prevention delivered through TikTok. Knowledge was assessed using a structured questionnaire before and after the intervention. Data normality was evaluated using the Shapiro–Wilk test, and differences in knowledge scores were analyzed using the paired samples t-test with a significance level of α = 0.05. The mean knowledge score increased from 12.31 ± 2.45 before the intervention to 17.94 ± 1.61 after the intervention. The Shapiro–Wilk test confirmed that the data were normally distributed (p > 0.05). Paired samples t-test demonstrated a statistically significant improvement in knowledge, with a mean difference of 5.63 (95% CI: 4.91–6.34; p < 0.001). The intervention also showed a very large effect size (Cohen's d = 2.74). These findings indicate that TikTok-based health education is effective in improving pregnant women's knowledge regarding abortion prevention and may serve as an innovative educational strategy to strengthen health promotion within antenatal care services.